Thinking About Dementia Culture, Loss, and the Anthropology of Senility - Leibing, Annette (Studies in Medical Anthropology, 2006)
Bringing together essays by nineteen respected scholars, this volume approaches dementia from a variety of angles, exploring its historical, psychological, and philosophical implications. The authors employ a cross-cultural perspective that is based on ethnographic fieldwork and focuses on questions of age, mind, voice, self, loss, temporality, memory, and affect.Taken together, the essays make four important and interrelated contributions to our understanding of the mental status of the elderly. First, cross-cultural data show that the aging process, while biologically influenced, is also culturally constructed. Second, ethnographic reports raise questions about the diagnostic criteria used for defining the elderly as demented. Third, case studies show how a diagnosis affects a patient's treatment in both clinical and familial settings. Finally, the collection highlights the gap that separates current biological understandings of aging from its cultural meanings.